2018
DOI: 10.1016/j.aprim.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Perfil clínico de pacientes con fibrilación auricular tratados con anticoagulantes orales de acción directa atendidos en atención primaria. Estudio SILVER-AP

Abstract: Patients treated with DOAC in Spain have a high thromboembolic risk. A significant proportion of patients receive a lower dose of DOAC than that recommended according to their clinical profile. Satisfaction and medication adherence are high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
1
2
0
5
Order By: Relevance
“…In this regard, the protocol asked for a consecutive recruitment of patients coming to the routine clinical visits, and in case of patients do not capable to answer the questions, the study provided the possibility for including the caregiver. Despite the study limitations, the collected results were coherent with the reported in similar studies, in both terms, patients profile [ 32 , 33 ] and reported preferences [ 22 , 24 , 29 ], minimising the impact of the study limitations and providing robustness to the presented results.…”
Section: Discussionsupporting
confidence: 83%
“…In this regard, the protocol asked for a consecutive recruitment of patients coming to the routine clinical visits, and in case of patients do not capable to answer the questions, the study provided the possibility for including the caregiver. Despite the study limitations, the collected results were coherent with the reported in similar studies, in both terms, patients profile [ 32 , 33 ] and reported preferences [ 22 , 24 , 29 ], minimising the impact of the study limitations and providing robustness to the presented results.…”
Section: Discussionsupporting
confidence: 83%
“…Accordingly, real-world studies evaluating DOACs in the Spanish population are scarce. A few retrospective studies have been published based on databases containing electronic health records [17,18,19,20,21] or prospective registries [11], but most of these studies have focused exclusively on the distribution of the different DOACs/doses prescribed and patients characteristics [17,18,19,20,21] and only a few have analyzed stroke and bleeding events [11,12,13,22]. To our knowledge, the study by Cerda et al [13], performed in a cohort of 1443 patients from a single center is the only one with a comparable methodology to ours, showing similar basal characteristics and follow-up of our cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The SILVER-AP study was an observational, cross-sectional, and multicenter study that included patients with NVAF attended by primary care physicians from those autonomous communities in which the primary care physician could prescribe DOACs directly (9 autonomous communities). Patients had to be on chronic treatment with anticoagulants, but on current treatment with DOACs for at least 3 months 2628…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it is important to analyze the clinical management of rivaroxaban not limited to a specific area or specialty in Spain. The aim of this analysis was to determine the clinical profile and use in clinical practice of patients taking rivaroxaban in Spain, using data from the following studies: HEROIC ( Perfil de pacientes con fibrilación auricular novalvular tratados con rivaroxaban en España: la desigualdad en el acceso a los anticoagulantes orales directos )23; EMIR ( Estudio observacional para la identificación de los factores de riesgo asociados a eventos cardiovasculares mayores en pacientes con fIbrilación auricular no valvular tratados con un anticoagulante oral directo Rivaroxaban )24,25; BRONCE-AP ( Estudio observacional de corte transversal para evaluar el uso de recursos y las características sociodemográficas y clínicas de los pacientes diagnosticados de FANV con riesgo de ictus o embolia sistémica, en tratamiento anticoagulante y que son atendidos en consultas de atención primaria )26,27; SILVER-AP ( Estudio observacional de corte transversal para evaluar las características sociodemográficas y clínicas de los pacientes diagnosticados de FANV con riesgo de ictus o embolia sistémica, que reciben tratamiento para el control adecuado de su coagulación y que son atendidos en consultas de atención primaria )2628; ALADIN ( Validación del cuestionario ACTS en pacientes con Fibrilación Auricular tratados con anticoagulantes orales en consultas de medicina interna y neurología de España )2931; ESPARTA ( Estudio sobre el seguimiento en la práctica clínica de las recomendaciones sobre el tratamiento con anticoagulantes orales en pacientes con fibrilación auricular de edad avanzada ) 3234. In addition, our data were compared with those of the XANTUS study15,35 and the ROCKET-AF trial 12…”
Section: Introductionunclassified